Soccer-based promotion of voluntary medical male circumcision: A mixed-methods feasibility study with secondary students in Uganda - Miiro, George; DeCelles, Jeff; Rutakumwa, Rwamahe; Nakiyingi-Miiro, Jessica; Muzira, Philip; Ssembajjwe, Wilber; Musoke, Saidat; Gibson, Lorna J.; Hershow, Rebecca B.; Francis, Suzanna; Torondel, Belen; Ross, David A.; et al. (PLoS ONE, 2017)
The Ugandan government is committed to scaling-up proven HIV prevention strategies including safe male circumcision, and innovative strategies are needed to increase circumcision uptake. The aim of this study was to assess the acceptability and feasibility of implementing a soccer-based intervention (ªMake The Cutº) among schoolboys in a peri-urban district of Uganda. The intervention was led by trained, recently circumcised ªcoachesº who facilitated a 60-minute session delivered in schools, including an interactive penalty shootout game using metaphors for HIV prevention, sharing of the coaches' circumcision story, group discussion and ongoing engagement from the coach to facilitate linkage to male circumcision. The study took place in four secondary schools in Entebbe sub-district, Uganda. Acceptability of safe male circumcision was assessed through a cross-sectional quantitative survey. The feasibility of implementing the intervention was assessed by piloting the intervention in one school, modifying it, and implementing the modified version in a second school. Perceptions of the intervention were assessed with in-depth interviews with participants. Of the 210 boys in the cross-sectional survey, 59% reported being circumcised. Findings showed high levels of knowledge and generally favourable perceptions of circumcision. The initial implementation of Make The Cut resulted in 6/58 uncircumcised boys (10.3%) becoming circumcised. Changes made included increasing engagement with parents and improved liaison with schools regarding the timing of the intervention. Following this, uptake improved to 18/69 (26.1%) in the second school. In-depth interviews highlighted the important role of family and peer support and the coach in facilitating the decision to circumcise. This study showed that the modified Make The Cut intervention may be effective to increase uptake of safe male circumcision in this population. However, the intervention is time-intensive, and further work is needed to assess the cost-effectiveness of the intervention conducted at scale.
Keywords: Soccer; Medical male circumcision; Students